Plan de capacitación para el talento humano del sindicato de choferes profesionales del cantón Valencia, provincia de Los Ríos, año 2013. - Rodríguez Rivera, Mayra Estefanía (2013)
This thesis took her place in the premises of the Trade Union of professional drivers of Valencia canton, located in the Avenue 13 December, Km 1, via a. Quevedo, in order to develop a training plan for the human resources of the institution, for which it was necessary to identify the main training needs of existing, was evaluated the knowledge of human talent and through the results the general training programmer was designed for the staff in order to strengthen the knowledge and optimize the development of activities in the organization. Within the methodological process to develop the training plan, took into account the following points: establish the objectives of the plan; Identify and clarify the activities necessary to achieve them; these activities in accordance with the human talent, resources, processes and development of actions, according to the planning group. To develop the study used two types of research; field, implemented in the Trade Union of professional drivers of the canton of Valencia, using the techniques of surveys and interviews, which were applied to the staff of the different areas of the institution; bibliographic type - documentary, based on texts, books and the internet, based on the object of study. Also used several methods; inductive, deductive and analytic, which enabled collecting primary and secondary information according to the theme. The literary review contributed to the accomplishment of this work, also collaborated with the structure of the training plan. In the Trade Union of professional drivers of Valencia Canton, were diagnosed with the absence of a training plan, which resulted in shortcomings in the administrative and operational development of human talent, reason why it has been decided to propose the implementation of this tool, with the fundamental aim of creating an environment in which employees can achieve their objectives of group in the shortest time seeks to improve the work performance, to achieve the goals and objectives established by the organization. The proposal "development of a training plan for the talent of the Trade Union of professional drivers of the Canton Valencia", leads to the innovation of knowledge, improve performance labor and therefore the quality of service to meet the needs of its partners. In short, it is important to mention that the work to be done in this institution allows strengthen knowledge and acquire expertise in the professional field.